The Energy Spectra of Electron Microbursts Between 200 keV and 1 MeV. Issue 11 (29th October 2021) - Johnson, A. T.; Shumko, M.; Sample, J.; Griffith, B.; Klumpar, D.; Spence, H.; Blake, J. B.
Abstract: This study investigates the energy spectrum of electron microbursts observed by the Focused Investigations of Relativistic Electron Burst Intensity, Range, and Dynamics II (FIREBIRD‐II, henceforth FIREBIRD) CubeSats. FIREBIRD is a pair of CubeSats, launched in January 2015 into a low Earth orbit, which focuses on studying electron microbursts. High‐resolution electron data from FIREBIRD‐II consist of 5 differential energy channels between 200 keV and 1 MeV and a > 1 MeV integral channel. This covers an energy range that has not been well studied from low Earth orbit with good energy and time resolution. This study aims to improve the understanding of the scattering mechanism behind electron microbursts by investigating their spectral properties and their relationship with the equatorial electron population under different geomagnetic conditions. Microbursts are identified in the region of the North Atlantic where FIREBIRD only observes electrons in the bounce loss cone. The electron flux and exponential energy spectrum of each microburst are calculated using a FIREBIRD instrument response modeled in GEANT4 (GEometry ANd Tracking) and compared with the near‐equatorial electron spectra measured by the Van Allen Probes. Microbursts occurring when the Auroral Electrojet (AE) index is enhanced tend to carry more electrons with relatively higher energies. The microburst scattering mechanism is more efficient at scattering electrons with lower energies; however, the difference in scattering efficiency between low and high energy is reduced during periods of enhanced AE. Key Points: We present a statistical study of the energy spectrum of electron microbursts observed by the FIREBIRD‐II CubeSats Individual microbursts contain more electrons at a higher Auroral Electrojet as well as relatively more high‐energy electrons The microburst scattering mechanism is more efficient at scattering low‐energy electrons